PEDAGOGICAL TOOLKIT OF NATIONAL-PATRIOTIC EDUCATION (Physical Culture and Sport: Scientific Perspective, 2023)
The article specifies the essence of patriotism as a spiritual and moral quality, social feeling, socio-cultural value. It was clarified that patriotism is the most important criterion of Ukrainian national and civic identity, its formation determines the readiness of the individual to fulfill the duty of protecting the independence of the state and its territorial integrity.Based on the normative-legal documents on the organization of national-patriotic education, its purpose, tasks and content have been specified and specified, taking into account the following vectors: civic-patriotic, spiritual-moral, military-patriotic, ecological; the pedagogical toolkits for its effective implementation in educational institutions was substantiated; it makes possibility to imagine the target, substantive and technological characteristics of national-patriotic education as an integral pedagogical phenomenon and socio-cultural process deeper and more comprehensively.
Keywords: national-patriotic education; patriotism; Ukrainian national and civic identity; pedagogical toolkits; students; forms and methods of education